2002
DOI: 10.2527/2002.8061638x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting animal performance during the grazing season in a mountain cattle production system1

Abstract: The factors influencing weight changes during the grazing season of Brown Swiss autumn-calving cows and Brown Swiss and Pirenaica spring-calving cows and their calves were studied over an 8-yr period in Spanish mountain conditions. The data set comprised 552 annual production cycles of cows that calved in two consecutive years. The animals grazed on alpine ranges during the summer and on forest pastures in the spring and autumn. They were housed during the winter and fed at different feeding levels (83 to 117%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
31
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 19 publications
11
31
0
1
Order By: Relevance
“…Over the past few decades these breeds have been bred specially for meat production, which ordinarily requires animals to mature more slowly, and as a consequence these breeds do indeed mature later (Gutié rrez et al, 2006). The degree of lipid accumulation was intermediate in the Pirenaica and Parda Alpina breeds, which, together with the Asturiana and Rubia Gallega breeds, are raised principally in northern Spain (Casasú s et al, 2002). A comparison of Pirenaica bulls and Holstein bulls, deemed to be an early-maturing breed, showed that the latter exhibited a higher degree of lipid accumulation than the former (Eguinoa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades these breeds have been bred specially for meat production, which ordinarily requires animals to mature more slowly, and as a consequence these breeds do indeed mature later (Gutié rrez et al, 2006). The degree of lipid accumulation was intermediate in the Pirenaica and Parda Alpina breeds, which, together with the Asturiana and Rubia Gallega breeds, are raised principally in northern Spain (Casasú s et al, 2002). A comparison of Pirenaica bulls and Holstein bulls, deemed to be an early-maturing breed, showed that the latter exhibited a higher degree of lipid accumulation than the former (Eguinoa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In European dry mountain areas, the harsh climate imposes long winter-housing periods for suckler cattle farms (Casasú s et al, 2002). In the Spanish Pyrenees, autumnborn calves are traditionally reared indoors with their dams and they are weaned at the start of the spring season (aged 5 months).…”
Section: Introductionmentioning
confidence: 99%
“…Stress response may also be influenced by breed, because genetic factors can be important in the neuroendocrine and metabolic adaptation to stressing conditions (García-Belenguer et al, 1996). Pirenaica and Parda de Montañ a breeds have similar mature weight but different milk production, calf growth (Villalba et al, 2000;Casasú s et al, 2002) and sensitivity to stress (Palacio, 2000). The objective of this study was to assess the effect of age at weaning on the physiological response, immune function, temperament and performance in calves of Parda de Montañ a and Pirenaica, two Spanish beef cattle breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Influence of temperature, season and breed on the indicators of the internal environment was studied, too (Doornenbal et al 1988;Thrall et al 2004;Grundwaldt et al 2005;Yokus and Cakir 2006;Ndlovu et al 2009). The concentration of metabolites in animals' blood is an important indicator associated with the production of particular animal products (Rueg et al 1992;Casasus et al 2002;Ban-Tokuda et al 2007). Determining indicators of the metabolic profile during the breeding season is helpful in diagnosing metabolic problems in animals (Jagos et al 1985;Verheyen et al 2007).…”
mentioning
confidence: 99%